Isoform- and cell-specific function of tyrosine decarboxylase in the Drosophila Malpighian tubule. - Blumenthal, E.M. (Journal of Experimental Biology, 2009)
The biogenic amine tyramine (TA) is a potent diuretic factor when applied to the Malpighian tubule (MT) of Drosophila melanogaster, stimulating both urine production and transepithelial chloride conductance. Isolated MTs can respond not only to TA but also to its precursor, tyrosine; this observation led to the proposal that MTs are able to synthesize TA from applied tyrosine through the action of the enzyme tyrosine decarboxylase (TDC). In the current study it is shown that the non-neuronal isoform of TDC, Tdc1, is expressed in the principal cells of the MT. A mutant allele of Tdc1, Tdc1(f03311), was identified that reduced expression of the mature Tdc1 transcript by greater than 100-fold. MTs isolated from Tdc1(f03311) homozygous flies showed no significant depolarization of their transepithelial potential (TEP) or diuresis in response to tyrosine while retaining normal sensitivity to TA. By contrast, a previously identified null mutant allele of the neuronal TDC isoform Tdc2 had no effect on either tyrosine or TA sensitivity. To determine in which cell type of the MT Tdc1 expression is required, flies were generated carrying a UAS-Tdc1 transgene and cell-type-specific Gal4 drivers on a Tdc1(f03311) homozygous background. Rescue of Tdc1 expression in principal cells fully restored sensitivity to tyrosine whereas expression of Tdc1 in stellate cells had no rescuing effect. It is concluded that synthesis of TA by Tdc1 in the principal cells of the MT is required for physiological responses to tyrosine. TA synthesis in the MT is the first reported physiological role for Drosophila Tdc1.